P26: EVALUATING AND DEVELOPING A TEACHING TOOL ON FAECAL INCONTINENCE IN THE UNDERGRADUATE MEDICAL CURRICULUM. (27th April 2021) - Li, CH; Parker, J; Reeve, N; Cornish, J
Abstract: Introduction: To evaluate the medical school undergraduate curriculum on faecal incontinence (FI) and develop an educational tool to improve the teaching on the subject. Method: Qualitative analysis of literature research and data collected from medical students via emails, questionnaires and focused group discussions. Result: FI has not been implanted into the undergraduate curriculum 12, 13 and there are variations in teaching on the topic in different medical schools. n= 111 medical students at Cardiff University responded to the survey. FI was reported to be overlooked compared to other types of bowel dysfunction. 38 students reported to have teaching on bowel incontinence, whereas 64 and 74 students had teaching on diarrhoea and constipation respectively. 77% of medical students would like more teaching on bowel incontinence. 9 students participated in a focused group discussion. An interactive e-learning module from Xerte was created based on the students' suggestions and were trialed by a separate cohort of students (n=20). All 20 students showed significant improvement of students' confidence in faecal incontinence (p <= 2.132e ∧-6 ) after completing the e-learning module. Conclusion: We recommend introducing the educational resource into the undergraduate curriculum of Cardiff University medical school, especially targeting the clinical year, a clear guidance for FI should be published by the relevant postgraduate healthcare faculties and consider assessing at which stage of the postgraduate training should FI be taught. Take-home message: Baseline knowledge of FI is poor. Lack of content in medical school curriculum and E learning modules potentially useful adjuncts.